If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.25(y + -4) + 0.03y = 0.18y + -0.05(40) Reorder the terms: 0.25(-4 + y) + 0.03y = 0.18y + -0.05(40) (-4 * 0.25 + y * 0.25) + 0.03y = 0.18y + -0.05(40) (-1 + 0.25y) + 0.03y = 0.18y + -0.05(40) Combine like terms: 0.25y + 0.03y = 0.28y -1 + 0.28y = 0.18y + -0.05(40) Multiply -0.05 * 40 -1 + 0.28y = 0.18y + -2 Reorder the terms: -1 + 0.28y = -2 + 0.18y Solving -1 + 0.28y = -2 + 0.18y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-0.18y' to each side of the equation. -1 + 0.28y + -0.18y = -2 + 0.18y + -0.18y Combine like terms: 0.28y + -0.18y = 0.1y -1 + 0.1y = -2 + 0.18y + -0.18y Combine like terms: 0.18y + -0.18y = 0.00 -1 + 0.1y = -2 + 0.00 -1 + 0.1y = -2 Add '1' to each side of the equation. -1 + 1 + 0.1y = -2 + 1 Combine like terms: -1 + 1 = 0 0 + 0.1y = -2 + 1 0.1y = -2 + 1 Combine like terms: -2 + 1 = -1 0.1y = -1 Divide each side by '0.1'. y = -10 Simplifying y = -10
| j+j-j=11 | | -16t^2+84t+112=0 | | 6.3/0.9-(-4.1)x(-0.4) | | 8y-2(5+2y)=7y-16 | | 2 = 12(9x+8) | | -3(3x-3)-9=-2(7x+3)-3 | | 16t^2+84t+112=0 | | 3x+6=27+y | | 7y+-42x+7=0 | | -8-6=7x-2-6x | | 6x-(8X+9)=2x-17 | | 9x+16y=-2 | | Sqrtx^2+7=x+1 | | 5*(x+8)=110 | | 26-u=234 | | 41.73/4.00x | | -4(3y+2x)= | | 70=164-v | | 6.78=2X/0.4-X | | 11x-67=77+2x | | x+x+1+x+2+x+3=-74 | | 3=23-5m | | -3(9+-2y+2.5z)+5y+2z=-27 | | 6(ax+3b)= | | 3+3x-1=9x+4-7x | | 14=4g-2 | | -4+(-24)=12 | | x-(3+x)+6=x-2[x-(3x+4)] | | (x-2)^1/2=(28-2x)^1/4 | | 8(3k-7)=64 | | 15x-6=360 | | x+x-1=2x+3 |